If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3t + 3 = t + 8 Reorder the terms: 3 + 3t = t + 8 Reorder the terms: 3 + 3t = 8 + t Solving 3 + 3t = 8 + t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-1t' to each side of the equation. 3 + 3t + -1t = 8 + t + -1t Combine like terms: 3t + -1t = 2t 3 + 2t = 8 + t + -1t Combine like terms: t + -1t = 0 3 + 2t = 8 + 0 3 + 2t = 8 Add '-3' to each side of the equation. 3 + -3 + 2t = 8 + -3 Combine like terms: 3 + -3 = 0 0 + 2t = 8 + -3 2t = 8 + -3 Combine like terms: 8 + -3 = 5 2t = 5 Divide each side by '2'. t = 2.5 Simplifying t = 2.5
| 14+a=2(a-4) | | 10x^3-7x-3=0 | | kx^2-kx^2=-1 | | X+35=6x | | 4-7a+15-8a-21= | | 1.5x+4=0.25x-3 | | 16h^4-8h^2+1=0 | | 0.875t-2=0.375t+9 | | 2(4x-1)+3x=-13o | | 22.67647059= | | 6=4*-10 | | y=29 | | 5x-4=x+32 | | 5x^4+16x^3+12x^2=0 | | 27a^3+64= | | x^2+3x+88=0 | | x(x+3)=88ft^2 | | 2x-9=57 | | 4(-2c+1)=3c-18 | | 28x^2-x-15=0 | | 12x^3-42x+18=0 | | 4x-9-12-3x=18 | | 14w^2+8w=0 | | 5a+3b+7a-4b= | | 10+4x=7-11x | | 4f^2-15f+14=0 | | 5(x+3)=4 | | 3(5x+2)=6(x+4) | | 3(3x+3)=-7(x+5) | | X^2-5x-2=o | | 6(2x+4)=-3(x+5) | | 18p-13=7+10p |